Is it worth considering circulating microRNAs in multiple sclerosis? - Ferdinand eJagot; Nathalie eDavoust (Frontiers in Immunology, 2016)
New evidence has highlighted that miRNA production and trafficking can be dysregulated in both autoimmmune and neurological disorders. Multiple sclerosis (MS) in particular is an autoimmune pathology leading to neurodegeneration. Profiling studies performed on cells derived from MS patients have described a dysregulated network of miRNAs in both immune and neural cells. Interestingly, new evidence has emerged showing that circulating miRNAs are also dysregulated in MS body fluids including plasma/serum and cerebrospinal fluid. This review summarizes the current scientific theories on the function of this altered circulating miRNA network. It builds up new insights about miRNA transfer mechanisms including extracellular vesicle trafficking involved in cell-to-cell communication and the possible physiopathological functions of these transfers in MS. Finally this review proposes that monitoring altered miRNA expression levels could serve as a potential biomarker read-out of MS subtype and severity.